ANALISIS TEKNIKAL SAHAM-SAHAM SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Yudono, Indratmo (Performance, 2010)
Research testing technical analysis trading strategy is to take samples of stocks from the company (issuer) mining sector from the first time listing until October 2008. This research focused on stock price movement patterns of the minor, intermediate and primary with dual technical analysis moving average crossover with stock prices that pass the test randomness of data. Is there a significant difference between the average return of the third period. Thus, investors who use technical analysis to the period of time can make a profit (return) the maximum. Research shows that of the 21 stocks pass the test of randomness of data (data is not random). While testing the difference in average return on average produce stock returns that are not significantly different at an alpha level of 5% confidence, at different time periods vary in technical analysis tool dual moving average crossover as well as in a period of industry in mining sector. This indicates that the average profit (return) to investors who use technical analysis of a dual moving average crossover with a different time period or a period of industry in the mining sector is no different.